Quantum-Chemical Study of the Coordination of Some Biguanides and their NDeprotonated Derivatives - AÏDOTE, François; KUEVI, Urbain; KPOTIN, ASSONGBA GASTON; KPOTA HOUNGUE, MAHOUGBE TATA ALICE; ATOHOUN, Guy Sylvain; MENSAH, JEAN-BAPTISTE (My University, 2018)
The biguanides [HN=C(NR1R2)-NH-C(NR3R4)= NH] constitute an important family of molecules used as drugs in the treatment of diabetes. The five nitrogen atoms are potential coordination sites since they each carry a free electron pair. In the state of complexes, the therapeutic properties of the active molecules increase considerably. Recent experiments with Zinc complexes on diabetic animals have been very successful. The present work deals with the Quanto-Chemical Study of the Coordination of some Biguanides such as biguanide, metformin and butformin. The objective is to determine the most favorable sites for the coordination of these ligands through the analysis of chemical properties that are coordinating indicators: the interatomic bond lengths, the atomic charges, the electrostatic potentials, the structures of boundary orbitals and atomic electrophilic supredelocalisability index. Calculations were performed by the DFT / B3LYP method in the 6-31G (d, p) database with the Gaussian 09 and 03 softwares and the DCENT-QSAR program. The sp2 nitrogen atoms have proved to be the most favorable coordination sites. Complexes of these ligands with Zn (II) were modeled.
Keywords: Coordination compounds; biguanides; anti-diabetic treatments; DFT / B3LYP / 6-31G (d; p) basis set